Responsabilidades civil e social da empresa na tutela do meio ambiente do trabalho na din??mica de sua cadeia produtiva - Melatti, Andr?? Vinicius (2017)
The present dissertation examines the sustainability of the development of organized economic activities in a network of suppliers, subcontractors and contracts, involving inputs needed to achieve the social object of the final destination company, verifying the concomitant search for economic, social and environmental aspects. It is based on the premise that guaranteeing a minimum level of quality, balance and environmental security is necessary for the realization of life at decent levels, placing the protection of the various aspects of the environment in the international legal order and in the Brazilian constitutional and jus-labor infraconstitutional plans, in order to promote, at all links in the modern production chain, the fundamental right to the environment of balanced, healthy and safe work. After discussing the governing principles of International Environmental Law, it is stated that the business agent must consider the internalisation of negative externalities caused by its economic activity, in favor of the socio-environmental well-being of the workers involved, which is why it must identify the interested parties with whom (stakeholders), through the analysis of the external environment affected by the development of its enterprise, promoting processes and techniques of sustainable management of suppliers, subcontractors and contracts. It states that any form of productive outsourcing, to be sustainable in the long term, must be maintained under strict socio-environmental control of the contracting company, in order to promote the rights necessary for the well-being and healthy quality of the worker's life, through the creation and maintenance of environments that can prevent accidents, injuries and occupational diseases, aiming at decent work, in the concept advocated by the International Labor Organization. At the end, it defends the hypothesis that the non-compliance with the legal obligation of environmental protection in the supply chain, by the company economically relevant in this dynamic, attracts the incidence of the institute of civil liability, covering the payment of damages for environmental damage, both individual and collective and material and moral.